Social Strength Based on Strength Family Institution - Sriwan, Sa-ard; Kenaphoom, Assoc. Prof. Dr. Sanya; Phoosing, Assoc. Prof. Dr. Pakdee (Journal for Developing the Social and Community, 2017)
When people come together and build relationships between each other, this relationships will be linked as stable map, so, if relationship is divided into these, it will be saw similar relationships, thus it is called "Social Institution", which serves needs of members’ society. Social institutions has their own customary rules and regulations such as economic, educational, religious institutions, etc. Family institution is union of people with love, bondage, interact each other. The family is the smallest institution but most important which is the first social unit to mold life and educate. Family is source of society helping human personality, build and develop qualities of life. There is question how can society be good, it depends on families which lived their own roles. That is the rule of law principle of virtue or doctrines of their religion that make happy. However, the benefits of social institution will be strengthened, prospered and happy, the political, religious institutions, etc., will also be affected in good way as well because of members’ family are good, morality, responsibility strictly following the role of institutions that will lead to be good life as well.